A strategy for the synthesis of cyclomatrix-polyphosphazene nanoparticles from non-aromatic monomers - Huang, Zhangjun; Van Sittert, Cornelia Gertina Catharina Elizabeth; Zheng, Feng; Chen, Shuangshuang; Lu, Xuemin; Lu, Qinghua (RSC, 2016)
Cyclomatrix-polyphosphazenes (C-PPZs) are a new class of nanomaterials that have attracted significant interest owing to their unique inorganic-organic hybrid structure and tunable properties. The limited success that has been achieved in producing C-PPZs from non-aromatic organic monomers is ascribed to an insufficient understanding of their polymerization mechanism. In this work, by using a new strategy termed solubility-parameter-triggered polycondensation, we demonstrate experimentally and computationally that C-PPZs nanoparticle synthesis from non-aromatic monomers is feasible and solubility-parameter (SP)-dependent. The precipitation polycondensation of C-PPZ occurs once the solution SP is outside a critical SP range, while within the critical range only oligomers are detected from the reaction; this SP-dependent rule is applicable for C-PPZ oligomers from both aromatic and non-aromatic monomers. The upper/lower critical SP values increase with the increase of organic monomer hydrophilicity. The morphologies of C-PPZ products exist as clusters or nanoparticles when the reaction solvent SP is controlled below the upper critical SP or exceeds the lower critical SP, respectively. This theory presents a feasible way to predict and determine the precipitation polycondensation conditions and product morphology of any novel C-PPZ nanomaterial